Basketball Athletes Optimal Physical Conditions: Pillars of Success in the Field - Natan Eleginta Tarigan; Petrus Elkana Nababan; Nurkadri Nurkadri; David Siahaan; Restu Siregar; Nicolas Sianturi (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Basketball athletes' success is largely dependent on being in top physical shape. This study outlines the fundamental components of physical fitness that significantly influence an athlete's performance in competition. The primary tenet of success on the court is optimal physical fitness, which is the focus of this study on basketball athletes. The technique examines three key factors: cardiorespiratory endurance, speed, and muscle strength. According to the study's findings, the average strength of the squat and bench press muscles was 105.1 kg and 82 kg, respectively. This shows the value of maintaining a balance between upper and lower body strength. Speed and agility go hand in hand, as evidenced by the average sprint and agility times of 4.45 and 8.45 seconds, respectively. The Beep Test level is 10.3, indicating the strength of physical endurance, while the average VO2max cardiorespiratory endurance is 41.3 ml/kg/minute. These findings suggest that improving the balance between muscle strength, quickness, and cardiorespiratory endurance is crucial for enhancing basketball athletes' performance. As a result, advice is given to coaches and athletes on how to create training plans with workouts that concentrate on these factors. As a result, athletes may perform at their peak on the field, respond quickly to obstacles, and produce their best work during competition.